Down with colonialism - Ho, Chi Minh 1890-1969.; Bello, Walden F. (London Verso, 2007)
Selections from the writings of Ho Chi Minh. Ho Chi Minh, the founder of the Vietminh and President of the Democratic Republic of Vietnam, having defeated Japanese and French colonialist became a hate figure of the USA during the Vietnam War. Anti-globalization activist Walden Bello shows why Ho Chi Minh should still be read by anti-imperialists the world over. -- Back cover.
Introduction -- 1. Speech at the Tours Congress -- 2. Indochina -- 3. The Anti-French resistance -- 4. Some considerations on the colonial question -- 5. Annamese women and French domination -- 6. An Open Letter to M. Albert Sarraut, Minister of Colonies -- 7. Murderous civilization! -- 8. The martyrdom of Amdouni and Ben-Belkhir -- 9. About Siki -- 10. Menagerie -- 11. The Counter-Revolutionary Army -- 12. The Workers' Movement in Turkey -- 13. Report on the National and Colonial Questions at the Fifth Congress of the Communist International -- 14. Lenin and the colonial peoples -- 15. Appeal made on the occasion of the founding of the Indochinese Communist Party -- 16. The Party's line in the period of the Democratic Front -- 17. Letter from abroad -- 18. Instructions for the setting up of the Armed Propaganda Brigade for the Liberation of Viet Nam -- 19. Appeal for general insurrection -- 20. Declaration of independence of the Democratic Republic of Viet Nam -- 21. To the People's Committees in the whole country (north, south, centre) and at all levels (province, district and village) -- 22. Appeal to compatriots to carry out destruction, to wage resistance war -- 23. Appeal issued after six months of resistance -- 24. Twelve recommendations -- 25. To the National Congress of Militiamen -- 26. To the 6th Congress of Party Cadres -- 27. To peasant cadres -- 28. Instructions given at the Conference Reviewing the Second Le Hong Phong Military Campaign -- 29. On the Fifth Anniversary of the August Revolution and National Day -- 30. Political report at the Second National Congress of the Viet Nam Workers' Party -- 31. The imperialist aggressors can never enslave the heroic Vietnamese people -- 32. To practise thrift and oppose embezzlement, waste and bureaucracy -- 33. Instructions given at a conference on guerrilla warfare -- 34. Report to the Third Session of the National Assembly -- 35. Report to the Sixth Plenum of the Viet Nam Workers' Party Central Committee -- 36. To the nation -- 37. Instructions given at the Conference Reviewing the Mass Education in the first half of 1956 -- 38. Consolidation and development of ideological unity among Marxist-Leninist parties -- 39. On revolutionary morality -- 40. Report on the draft Amended Constitution -- 41. Thirty years of activity of the Party -- 42. The path which led me to Leninism -- 43. The Chinese Revolution and the Vietnamese Revolution -- 44. Address to the Sixth Session of the Second National Assembly of the Democratic Republic of Viet Nam -- 45. Appeal to compatriots and fighters throughout the country -- 46. Talk to district cadres attending a training class -- 47. Elevate revolutionary ethics, make a clean sweep of individualism -- 48. Appeal on the occasion of 20 July 1969 -- 49. Testament.
Keywords: Anti-imperialist movements -- Vietnam; Vietnam -- Politics and government -- 20th century